ПЕРЕДАВАННЯ ВЕЛИКОЇ ЕНЕРГІЇ В НАКОПИЧУВАЛЬНИЙ КОНДЕНСАТОР ВИСОКОВОЛЬТНИХ ГЕНЕРАТОРІВ РОЗРЯДНИХ ІМПУЛЬСІВ З ТРАНСФОРМАТОРАМИ ТЕСЛА - Щерба, А.А.; Ломко, М.О. (Інститут електродинаміки Національної академії наук України, 2019)
The processes of wireless transmission of high energy to the reservoir capacitor by means of its charging to a high voltage by long-continued low charging displacement current, which flows through the intermediate partial (stray) capacitance, are investigated. The analytical dependences of the time variation of the charge voltage of the reservoir capacitor are proposed. The features of the charging of a capacitive storage through a partial capacitance, which are related to the influence of the configuration of its plates on the voltage value and the charging duration of the reservoir capacitor, are investigated. References 18, figures 4, table.